Speeches & Letters of Abraham Lincoln, 1832-1865 - Lincoln, Abraham, 1809-1865; Roe, Merwin (Salt Lake City, UT : Project Gutenberg, 2005)
"Speeches & Letters of Abraham Lincoln, 1832-1865" by Abraham Lincoln is a collection of historical speeches and letters authored by the 16th President of the United States during the mid-19th century. The compilation aims to provide insight into Lincoln$1 (Bs thoughts and convictions on critical issues facing the nation, touching on his journeys from humble beginnings to becoming a prominent figure in American history. Primarily focused on political ideals, justice, and morality, this volume highlights the essence of Lincoln's character and the significant matters of his time, including slavery and national governance. The opening of this collection features a rich introduction by James Bryce, who contextualizes Lincoln's impact both within America and globally, emphasizing his reputation as a beloved leader crucial to the politics of his era. Lincoln's early public speech on education displays his earnestness and aspiration for moral development among citizens, while a subsequent letter reveals his candid acknowledgment of political challenges. His reflections are marked by humility and sincerity, aiming to engage common people while expressing profound ideas about justice, governance, and societal responsibilities. The manuscripts set the stage for a deeper understanding of his speeches that follow, which address more weighty subjects like abolition and the preservation of the Union during a tumultuous period in American history. (This is an automatically generated summary.)s
Release date is 2005-01-17
E-text prepared by Melanie Lybarger, Suzanne Lybarger, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Speeches, addresses, etc., American; Lincoln, Abraham, 1809-1865 -- Oratory; Lincoln, Abraham, 1809-1865 -- Correspondence